Uma história ambiental da Floresta Nacional de Passo Fundo: 1946-2011 - Sá, Débora Nunes de (2017)
Located at Mato Castelhano city, in the Rio Grande do Sul state, the Passo Fundo National Forest, Conservation Unit of Sustainable Use, has a surface with 1275 hectares, and, although is placed in the Ombrófila Mista Forest (araucaria Forest), only 354,80 hectares of its total area keep this remaining kind of vegetation. Has important representation at the sustainable handling of lumber species and at the regional biodiversity conservation. It history started at 1940 decade, when the National Pine Institute, a parastatal organ, implement, as a part of its “reforestation” politics (monocultures of trees), the foundation of Forestry Parks at South of Brazil, with the objective to study plantation techniques, handling and harvest of the native species Araucaria angustifolia. It was created in 1946, and then located in the Passo Fundo city, the José Segadas Viana Forestry Park, that after was renamed as Passo Fundo Forest Park. This research studies its historical path, since the Forestry Park up to the Handling Plan implementation in 2011 that defined the actual practices of forestry handling and management. Use the Regional and Environmental History approach and does a phytogeographical overview combined area of the Unit, in other words, consider the natural occurrence of the Ombrófila Mista Forest region and the social and economic relations – that participate of space construction –, that stablished from the Unit practices. It has as objective, still, study the transformations occurred in the landscape, the initiatives adopted to disclosure of technical knowledge acquired during the plantation experiments at the analyzed period, and the functions accept by the Unit over the time. Concluded that occurs several transformations at the Passo Fundo National Forest landscape, due the legal changes end the development of the Conservation Unit functions that become its landscape, in the most of part, building and handling through the human actions.